176 views
4 votes
How do I solve this, pretty urgent please. ​

How do I solve this, pretty urgent please. ​-example-1
User Rosalynn
by
7.5k points

1 Answer

5 votes

Answer:

  • 1

Explanation:

Substitute:


  • x^(0.5) = y

Then the expression becomes:


  • ((1+y^3)/(1-y+y^2)-y) (1-y^2)/(1-y) -y=\\

  • (((1+y)(1-y+y^2))/(1-y+y^2)-y) ((1-y)(1+y))/(1-y) -y=

  • (1+y-y)(1+y)-y=

  • 1(1+y)-y=

  • 1+y-y=
  • 1

The result is 1 regardless the value of x other than 1.

User Variax
by
7.2k points